Exploring physical therapists' perceptions of mobile application usage utilizing the FITT framework. (3rd April 2017) - Noblin, Alice; Shettian, Madhu; Cortelyou-Ward, Kendall; Schack Dugre, Judi
ABSTRACT: Primary Objective : The use of mobile apps in clinical settings is becoming a widely accepted tool for many healthcare professionals. Physical therapists (PTs) have been underresearched in this area, leaving little information regarding the challenges in using mobile apps in the PT environment. The FITT framework provides a theoretical underpinning for this investigation. Research Design and Methods : A survey was developed based on the FITT framework and research questions. Licensed PTs in attendance at the FPTA conference were asked to complete the survey. A descriptive analysis was conducted for the study and demographic variables. A factor analysis was performed to determine the appropriateness of the FITT framework. Main Outcome and Results : The individual-technology dimension showed the best fit to the framework, with the weakest fit being the individual-task dimension. The majority of PTs surveyed do not currently use apps in their professional practice nor do they feel that their organizational leadership endorses app usage. Conclusions : The integration of mobile apps into physical therapy practice can improve the standard of care. Additional apps and marketing of these apps could elevate use of this technology. However, leadership support with the necessary resources for app usage will be key to improved overall FITT.